Relationship between Cadmium Fractions Obtained by Sequential Extraction of Soil and the Soil Properties in Contaminated and Uncontaminated Paddy Soils - Toshimitsu Honma; Hirotomo Ohba; Tomoyuki Makino; Takuji Ohyama (Journal of Chemistry)
The method for the sequential extraction of cadmium from soil was adapted to investigate the relationship between different chemical forms of cadmium in soils and the soil properties of Cd-contaminated and uncontaminated paddy soils. Air-dried soil samples from each field site were sequentially fractionated into five forms: exchangeable Cd, inorganically bound Cd, organically bound Cd, oxide-occluded fraction, and residual Cd. The average and range of soil properties such as pH, total C, total N, CEC, exchangeable Ca, Mg, K, base saturation, available phosphate, particle size distribution, free iron oxide, oxalate extractable Al, and Fe were somewhat similar between uncontaminated and contaminated soils. The average total Cd in uncontaminated and contaminated soils was 0.26 and 0.65 mg kg−1, respectively. The proportions of soil Cd fractions did not differ between the uncontaminated and contaminated soils, although the Cd concentration of several fractions in contaminated soils was statistically higher than those in uncontaminated soils except for residual fraction. The proportion of exchangeable Cd was correlated with the CEC and phosphate absorption coefficient in contaminated soil but not in uncontaminated soil. Thus, soil properties appear to affect the proportions of soil Cd fractions in contaminated soil and should be considered when evaluating soil Cd mobility.